2023
DOI: 10.1136/bmjopen-2022-065759
|View full text |Cite
|
Sign up to set email alerts
|

Improving family functioning and reducing violence in the home in North Kivu, Democratic Republic of Congo: a pilot cluster-randomised controlled trial of Safe at Home

Abstract: ObjectiveTo test the effectiveness of the Safe at Home programme which was developed to improve family well-being and prevent multiple forms of violence in the home.DesignWaitlisted pilot cluster randomised controlled trial.SettingNorth Kivu, Democratic Republic of Congo.Participants202 heterosexual couples.InterventionThe Safe at Home programme.Primary and secondary outcome measuresThe primary outcome was family functioning, with secondary outcomes of past-3 month co-occurring violence, intimate partner viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Interventions focused on the relationship between men’s experiences of interpersonal violence and men’s use of IPVAW in conflict-affected settings are relatively rare. One recent exception is Safe at Home, a discussion group intervention in DRC, that explicitly recognized shared structural drivers for IPV and harsh parenting [ 19 ], thereby addressing multiple interpersonal violence exposures (e.g., child abuse and witnessing IPVAW) that could contribute to IPVAW use in the present and subsequent generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions focused on the relationship between men’s experiences of interpersonal violence and men’s use of IPVAW in conflict-affected settings are relatively rare. One recent exception is Safe at Home, a discussion group intervention in DRC, that explicitly recognized shared structural drivers for IPV and harsh parenting [ 19 ], thereby addressing multiple interpersonal violence exposures (e.g., child abuse and witnessing IPVAW) that could contribute to IPVAW use in the present and subsequent generations.…”
Section: Discussionmentioning
confidence: 99%
“…Dedicated attention to gender norms and attitudes in IPV interventions in conflict-affected settings is critical. Although interventions focusing on gender inequitable attitudes and related social norms have shown mixed effects in controlled studies, some studies have observed robust effects [ 19 ] or changes in factors that may precede IPV, including changes in attitudes toward violence 12. Our findings suggest targeting gender inequitable attitudes alongside mental health may be a useful strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to addressing GBV shown to successfully reduce rates of IPV outside of humanitarian settings includes adapting programs that used group learning and engaged partners through community gender dialogues [ 12 , 13 ]. Recent evidence from the ‘safe at home’ trial in the Democratic Republic of Congo (DRC) finds that single-sex discussion groups for couples significantly reduced the risk of IPV for women and harsh discipline for children [ 14 ]. However, in another study amongst conflict affected populations in the DRC, similar gender dialogue trainings with men alone have not been found to reduce IPV [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, engaging men led to no promising impacts on women’s economic empowerment and did not address NPV. These interventions are also extremely resource and time intensive and require participants to attend upto 29 weekly sessions over a period of 6–8 months [ 14 ].…”
Section: Introductionmentioning
confidence: 99%